a - Farida Sutowo Putri; Santamoko, Ruby (Fakultas Bisnis, 2026)
This study analyzes the effect of several financial ratios on stock prices in the Indonesian banking sector. The research focuses on Price to Book Value (PBV), Loan to Deposit Ratio (LDR), Return on Equity (ROE), and Earnings Per Share (EPS) for bank companies listed on the Indonesia Stock Exchange (IDX) during the span of 2020–2024. A quantitative approach was applied using secondary data sourced from annual financial reports and stock closing prices. The sample consists of 18 banks with a total of 90 observations, analyzed through descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing using Eviews 9. The results show that PBV, LDR, and ROE have significant effects on stock prices, with determination coefficients of 28.2%, 3.80%, and 43.48%, respectively, and p-values below 0.05. EPS, however, records a determination coefficient of 3.69% and is not significant, as indicated by a p-value of 0.3819. Simultaneously, the four variables collectively influence stock prices, demonstrated by a determination coefficient of 51.83% and a p-value of 0.000. In conclusion, PBV, LDR, and ROE play important roles in explaining stock price variations in the banking industry. The findings provide useful insights for investors and market analysts when considering investment decisions.